Performance of CO1 and ITS2 nested PCR in molecular identification of ordinary scabies (Sarcoptes scabiei var. hominis) - Gita Dwi Prasasty; Miftahurrizqiyah Miftahurrizqiyah; Chairil Anwar; Dwi Handayani; Dalilah Dalilah; Ahmad Ghiffari; Inda Astri Aryani; Nunuk Dyah Retno Lastuti; Afiat Berbudi (Universitas Gadjah Mada, 2021)
Scabies is a global disease with a high prevalence, causing morbidity and even mortality, especially in poor and developing countries. However, it is often misdiagnosed due to varied and unspecified lesions. The gold standard technique for diagnosis is a microscopic examination, which requires experienced experts in finding mites, mainly in ordinary scabies. CO1 and ITS2 genes have been widely used in molecular identification to detect Sarcoptes scabiei and its variants. This study aimed to determine and compare the sensitivity and specificity of CO1 and ITS2 S. scabiei genes to the microscopic examination of scabies skin scrapings. The skin scrapings of 52 subjects with scabies diagnosed by anamnesis, physical examination, and dermoscopic examination were examined under a microscope and analyzed by nested PCR. The diagnostic test result showed that the sensitivity of nested PCR of both CO1 and ITS2 genes to micro‐ scope examination was 100%. However, the specificity of both CO1 and ITS2 nested PCR was poor (24% and 0%). Hence, CO1 and ITS2 nested PCR could be more suitable for screening ordinary scabies in humans than the microscopic examination.